Silence of α1-Antitrypsin Inhibits Migration and Proliferation of Triple Negative Breast Cancer Cells - Zhao, Zhijing (Med Sci Monit, 2018)
BACKGROUND: α1-antitrypsin (α1-AT) is highly expressed in many tumors. However, to the best of our knowledge, its relationship to triple negative breast cancer (TNBC) has not yet been studied. Thus, in this research we first explored the influence of α1-AT silencing on the abilities of migration and invasion, and then further study its molecular mechanism in TNBC cells. MATERIAL/METHODS: The viability of MDA-MB-231 cells were detected using cell counting kit-8 (CCK-8). The abilities of migration and invasion were examined by Transwell assay. The metastasis-related factors were tested respectively by quantitative real-time PCR (qRT-PCR) and western blot assays. RESULTS: Our study results showed that α1-AT level in TNBC tissues was higher than non-triple negative breast cancer (n-TNBC) and adjacent normal breast tissues. The high expression of α1-AT was linked to type of cancer, tumor size, TNM stage and metastasis, but was not correlated with α1-AT expression and age. si-α1-AT suppressed the viability, migration, and invasion of cells. While si-α1-AT upregulated E-cadherin and the tissue inhibitor of metalloproteinases-2 (TIMP-2) levels, it downregulated metastasis associated 1 (MTA1), matrix metallopeptidase 2 (MMP2), phosphorylated-mammalian target of rapamycin (p-mTOR), phosphorylated-protein kinase B (p-Akt), and phosphorylated-phosphatidylinositol 3 kinase (p-PI3K) levels. We also found that the PI3K/Akt/mTOR pathway activator reversed the role of si-α1-AT in metastasis-related factors. CONCLUSIONS: α1-AT was highly expressed in TNBC tissues, and its silencing suppressed the abilities of migration and invasion in TNBC cells and downregulated the PI3K/Akt/mTOR pathway. Thus, α1-AT may have a potential therapeutic effect on TNBC.